DNA repair after oxidative stress: current challenges (2017)
ABSTRACT: Reactive oxygen and nitrogen species damage cellular macromolecules including DNA. Cells have a robust base excision repair pathway to deal with this damage in both nuclear and mitochondrial genomes. However, mitochondria lack nucleotide excision repair. Evidence suggests that chronic oxidative stress can induce protective pathways lowering genotoxicity. Understanding oxidant injury to DNA and its repair is critical for our understanding the pathophysiology of a wide range of human disorders.